2019
DOI: 10.1155/2019/3953807
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Analysis of the Efficacy and Safety of Video Capsule Endoscopy in Patients with Implantable Cardiac Devices

Abstract: Background. To date, video capsule endoscopy (VCE) is still contraindicated by the FDA and the main manufacturers of Cardiac Implantable Electronic Devices (CIED) in patients with CIED, given a theoretical electromagnetic interference and possible device malfunction. Objectives. The objective of this study was to assess the safety profile and efficacy of VCE in patients with implantable cardiac devices through analyzing the risk of mutual interference. Methods. A systematic review of PubMed, Web of Science, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Открытым остается вопрос о применении видеокапсул у пациентов с кардиостимуляторами. Существуют публикации, подтверждаю щие безопасность выполнения видеокапсульной диагностики у данной группы пациентов, но в нашем исследовании пациентов с кардиостимуляторами не было [13,14].…”
Section: применение видеокапсульной эндоскопии в диагностике анемии и...unclassified
“…Открытым остается вопрос о применении видеокапсул у пациентов с кардиостимуляторами. Существуют публикации, подтверждаю щие безопасность выполнения видеокапсульной диагностики у данной группы пациентов, но в нашем исследовании пациентов с кардиостимуляторами не было [13,14].…”
Section: применение видеокапсульной эндоскопии в диагностике анемии и...unclassified
“…There is currently a lack of data regarding the safety of CE in pregnant women. Implanted cardiac devices like pacemakers or cardioverters were initially considered a contraindication, while subsequent studies have dispelled concerns about potential dysfunction in either the capsule or cardiac devices [14]; even so, manufacturers still maintain this contraindication. The use of a remote control for insulin infusion pumps has been suggested to potentially interfere with the CE transmission [15].…”
Section: Small Bowel Exploration-between Revelations and Unanswered I...mentioning
confidence: 99%
“…It has been suggested that there may be a theoretical risk of EMI with capsule endoscopy, but European guidance and a review of the available literature show no evidence of any clinical risk [22,23]. Image quality may be affected rarely.…”
Section: Capsule Endoscopymentioning
confidence: 99%